PENGARUH LINGKUNGAN KELUARGA DAN KEMANDIRIAN BELAJAR TERHADAP MOTIVASI SISWA DAN IMPLIKASINYAPADA HASIL BELAJAR (Penelitian Survey Siswa di kelas XII SMAN 8 Tasikmalaya Pada Mata Pelajaran Ekonomi) - Wulan Rif’a Nur Sani; Yoni Hermawan; Ai Nur Solihat (JOURNAL SAINS STUDENT RESEARCH, 2024)
The formulation of the problem in this study concerns how the influence of the family environment on student learning motivation, how the influence of student independence on student learning motivation, how the influence of student motivation on learning outcomes, how the influence of the family environment and student independence on student motivation, how the influence of the family environment and independence students on student learning outcomes, the influence of the family environment on student motivation and its implications for learning outcomes, how does student independence affect student motivation and its implications for learning outcomes and the influence of the family environment and student independence on student motivation and the implications for student learning outcomes. The research method used in this study is using descriptive quantitative research methods, with a correlational study type, the sampling process used in this research is the sample. It was concluded that there is a significant influence between the family environment and student independence on learning motivation and the implications for learning outcomes. So overall it shows that there is a relationship and influence between variables and has a significant influence, thus the influence of the family environment and independent learning on student motivation and its implications for student learning outcomes has a significant influence with a strong relationship level, and the correlation is significant.